RELEVANSI KRITIK BUDAYA SIRI SEBAGAI MAKNA ESTETIK ETOS KERJA DALAM NOVEL PULAU KARYA ASPAR PATURUSI PADA MASYARAKAT BUGIS-MAKASSAR DI KOTA TERNATE - NFN Wildan (Balai Bahasa Sulawesi Selatan, 2011)
Through the novel Pulau, Siri culture with its humanistic values that direct to work ethos growth is reconstructed. This form of reconstruction and solution to current situations through the aesthetics structure of the novel Pulau is without decreasing the values reflected in Siri culture. Through sociological theory of literature, Siri culture as expected to develop the spirit of work ethos correlate positively with economy activities of Bugis-Makassar migrant society in Ternate of North Maluku. The emergence of (the spirit of work ethos is not because of the obligation to save lives, but it is to show prestige through the success of established economy. The aim of this research is to reveal and explain the falshback of aesthetical values content in 'Siri' culture (budaya Siri') viewed from cultural critcs of Bugis-Makassar tribes. In addition, this research is also aimed to offer solutions and function of aesthetical critics in